PENGARUH PERILAKU BIAYA DALAM HUBUNGANNYA DENGAN PERUBAHAN VOLUME KEGIATAN PERUSAHAAN - Irwanty, Agnes; Ramadhani, Fitri; Gusna Putri, Rika; Hetri Suriyanti, Linda (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2021)
This study aims to provide an explanation of changes in company volume in terms of cost behavior. The results of this research can be used by companies to determine selling prices because selling prices affect sales volumes, sales volumes affect production volumes, and production volumes affect costs. And companies must be able to calculate and classify costs as accurately as possible so that the company knows in detail how much it costs and can help management increase profits. The research method used in this research is the decriptif method in which the writer collects data from the company, observes company activities, and interviews with sections related to the problem discussed, and studies lecture notes and other references to support this research. Research conducted gives the results that so far, the company has never conducted an analysis of profits using the method of cost-volume-profit analysis. Through this research we as the authors analyze and classify costs that are grouped into variable costs and fixed costs. The results of the study are based on October, November, and December 2019 because if there are some improper costs in the way they are classified, it can affect the size of the company's profits.